Type II Secretion Promotes Bacterial Growth within the Legionella-Containing Vacuole in Infected Amoebae - White, Richard C. (Infect Immun, 2019)
It was previously determined that the type II secretion system (T2SS) promotes the ability of Legionella pneumophila to grow in coculture with amoebae. Here, we discerned the stage of intracellular infection that is potentiated by comparing the wild-type and T2SS mutant legionellae for their capacity to parasitize Acanthamoeba castellanii. Whereas the mutant behaved normally for entry into the host cells and subsequent evasion of degradative lysosomes, it was impaired in the ability to replicate, with that defect being first evident at approximately 9 h postentry. The replication defect was initially documented in three ways: by determining the numbers of CFU recovered from the lysates of the infected monolayers, by monitoring the levels of fluorescence associated with amoebal monolayers infected with green fluorescent protein (GFP)-expressing bacteria, and by utilizing flow cytometry to quantitate the amounts of GFP-expressing bacteria in individual amoebae. By employing confocal microscopy and newer imaging techniques, we further determined the progression in volume and shape of the bacterial vacuoles and found that the T2SS mutant grows at a decreased rate and does not attain maximally sized phagosomes. Overall, the entire infection cycle (i.e., entry to egress) was considerably slower for the T2SS mutant than it was for the wild-type strain, and the mutant’s defect was maintained over multiple rounds of infection. Thus, the T2SS is absolutely required for L. pneumophila to grow to larger numbers in its intravacuolar niche within amoebae. Combining these results with those of our recent analysis of macrophage infection, T2SS is clearly a major component of L. pneumophila intracellular infection.